Plant spirit shamanism: traditional techniques for healing the soul - Heaven, Ross (Destiny Books, 2006)
Nothing is hidden : how plants heal -- The Shaman's diet : listening to the plants -- Plants of vision : sacred hallucinogens -- Healing the soul -- Pusangas and perfumes : aromas for love and wholeness -- Floral baths : bathing in nature's riches -- The scream of the mandrake